2020
DOI: 10.2471/blt.20.255489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of accessing antenatal care information via social media platforms supports mental wellbeing in COVID-19 epidemic

Abstract: DISCLAIMER This paper was submitted to the Bulletin of the World Health Organization and was posted to the COVID-19 open site, according to the protocol for public health emergencies for international concern as described in Vasee Moorthy et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
1
23
1
1
Order By: Relevance
“…For pregnant women, social networking sites and the Internet provided access to the information they need on their own. In China, antenatal health care information disseminated by hospitals using social media platforms was associated with a lower risk of stress, anxiety, and depression among pregnant women ( Jiang et al, 2020 ). Therefore, the use of social media in Japan as a means of disseminating antenatal health care information can decrease anxiety among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For pregnant women, social networking sites and the Internet provided access to the information they need on their own. In China, antenatal health care information disseminated by hospitals using social media platforms was associated with a lower risk of stress, anxiety, and depression among pregnant women ( Jiang et al, 2020 ). Therefore, the use of social media in Japan as a means of disseminating antenatal health care information can decrease anxiety among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…In various countries, pregnant women have refrained from visiting healthcare facilities for fear of infection due to hospital visits, or have felt isolated from social support networks and healthcare facilities designated for pregnant women suspected of having COVID-19. A study of pregnant Chinese women has shown that the perceived stress, depression, and anxiety of pregnant women in a pandemic situation are higher than those of normal pregnant women ( Jiang et al, 2020 ). On a couple level, wives’ depression, anxiety, suicide intention, mental health quality of life, and preventive COVID-19 behaviors are associated with husbands’ anxiety ( Ahorsu et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…in China [9]. In view of recent studies on social media's effects on risk communication [11,12], we combined social media data from given publications via a scoping review method and these captured by Zhongyun Big Data Platform [10]. Information released by o cial channels was collected by the Parehub tool.…”
Section: Methodsmentioning
confidence: 99%
“… 14–17 Despite the large and rapidly rising number of COVID-19 and resulting deaths, there are limited data about the clinical characteristics of pregnant women with the disease. 2 ,– 18–21 Although pregnant women do not seem to have an increased susceptibility to COVID−19 or more severe complications than non-pregnant adults, the available studies suggest that they may have the risk of adverse pregnancy outcomes. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%